Pengaruh Gaya Mengajar Latihan Terhadap Gerak Dasar Pada Servis Bawah Dalam Permainan Bola Voli Peserta Didik Kelas VIII SMP Negeri 3 Tondano - Ika Putri; Edita A.M. Pinangkaan; Eduard E. Kumenap (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study aims to test the application of teaching styles in improving the basic underhand serve in volleyball. The method used in this research is the experimental method. The sample used in this study consists of eighth-grade students from SMP Negeri 3 Tondano for the 2024/2025 academic year, totaling 20 samples, divided into two groups: the experimental group with a teaching style training consisting of 10 samples and the control group that did not receive treatment, also consisting of 10 samples. The research was conducted over one month with a frequency of three times a week. The research design used is a "Randomized control group pre-test and post-test design." The instrument used in this research is the "basic underhand serve movement test in volleyball." The data collection technique in this study is by conducting pre-tests and post-tests of the basic underhand serve movement in volleyball for both groups. The research hypothesis is "The application of teaching styles in training has an impact on the improvement of the basic movement of the underhand serve in volleyball for eighth-grade students at SMP Negeri 3 Tondano." The data analysis technique used is the t-test statistical analysis technique. Before the t-test is conducted, it is preceded by the analysis requirement tests, namely the data normality test and the variance homogeneity test. From the hypothesis testing calculations, thitung was obtained with a value of 6.45. Based on the t distribution table at 0.05 with degrees of freedom nl + n2-21010-218, the t-table value obtained is 2.101. So thitung is greater than ttabel, namely thitung = 6.45 and trabel = 2.101. Based on the testing criteria, if thitung is greater than ttabel (thitung table), then Ho is rejected, which means HA is accepted. The results of this study show that the average improvement in the mastery of the underhand serve basic movement in volleyball for the experimental group using the training teaching style is better than the average improvement in the mastery of the underhand serve basic movement in volleyball for the control group that did not receive the treatment. The conclusion of this study is that there is an influence of the application of the training teaching style on the improvement of basic underhand serve skills in volleyball among the eighth-grade students of SMP Negeri 3 Tondano